1984
DOI: 10.2105/ajph.74.7.668
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of drug use from adolescence to young adulthood: II. Sequences of progression.

Abstract: Major pathways of progression among legal, illegal. and medically prescribed psychoactive drugs from adolescence to young adulthood are described. The data are based on a follow-up cohort of former adolescents representative of high school students in grades 10 and 11 in New York State who were reinterviewed nine years later at ages 24-25. Various models of progression are tested for their goodness of fit. The patterns formerly observed in adoles- IntrodiuctionStages of involvement in legal and illegal drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
1
4

Year Published

1986
1986
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(149 citation statements)
references
References 23 publications
7
137
1
4
Order By: Relevance
“…This developmental sequence of drug involvement has been referred to as the Gateway Effect or Gateway Hypothesis (Kandel 1975Yamaguchi 1984). Nicotine is one of the most commonly used drugs of abuse.…”
mentioning
confidence: 99%
“…This developmental sequence of drug involvement has been referred to as the Gateway Effect or Gateway Hypothesis (Kandel 1975Yamaguchi 1984). Nicotine is one of the most commonly used drugs of abuse.…”
mentioning
confidence: 99%
“…Big influence on it, besides parents, has peers and older siblings [3,40]. Smoking not only represents a risk for the health but as earlier research has shown, smoking in adolescence results in a greater risk of alcohol consumption and psychoactive drugs [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…This idea suggests that a progressive and hierarchical sequence of stages of drug use can be described [74][75][76]. The basic premise of the developmental stage hypothesis is that involvement in various classes of drugs follows definite pathways and individuals who ingest one drug are at risk of progressing to the use of another drug [74].…”
Section: The Gateway Hypothesismentioning
confidence: 99%